2018
DOI: 10.15537/smj.2018.5.22043
|View full text |Cite
|
Sign up to set email alerts
|

Walking-based activity and sedentary behavior in Saudi males with chronic obstructive pulmonary disease

Abstract: ObjectivesTo compare walking-based activity and sedentary behavior between males with chronic obstructive pulmonary disease (COPD) and healthy controls and to examine the association between dyspnea with time spent in walking-based activity and sedentary behavior in males with COPD.MethodsThis cross-sectional study of 30 males with COPD (age 62.0±5.0 years; forced expiratory volume in one second [FEV1] 46±15% predicted) and 29 healthy controls (age 63.0±4.3 years; FEV1 91±5% predicted) was conducted at the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
5
1
1
Order By: Relevance
“…The time spent in medium walking in our study (0 [1] min) was even less in comparison to the time spent in medium walking in male adults with stable COPD (5 Ϯ 4 mins). 29 Our data show that walking in adult subjects hospitalized with CAP was accumulated in very short bouts. This is notable because the subjects included in these analyses received, on average, 2 (3) occasions of service by a physiotherapist.…”
Section: Discussionmentioning
confidence: 60%
“…The time spent in medium walking in our study (0 [1] min) was even less in comparison to the time spent in medium walking in male adults with stable COPD (5 Ϯ 4 mins). 29 Our data show that walking in adult subjects hospitalized with CAP was accumulated in very short bouts. This is notable because the subjects included in these analyses received, on average, 2 (3) occasions of service by a physiotherapist.…”
Section: Discussionmentioning
confidence: 60%
“…Studies were conducted in Australia [ 6 , 9 , 10 , 11 , 22 , 23 ], Austria [ 24 ], Brazil [ 5 , 12 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], Canada [ 38 ], Germany [ 39 ]. Greece [ 40 ], Japan [ 41 ], Korea [ 42 ], the Netherlands [ 43 , 44 ], Portugal [ 45 , 46 ], Saudi Arabia [ 47 ], Sweden [ 48 ], United Kingdom [ 49 ], and the United States of America [ 50 , 51 ]. The total number of participants across 36 studies was 3914 (56% males), and the mean ± SD for age was 67 ± 8 years.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, researchers found that older adults with chronic disease in Saudi Arabia spent less time on walking-related activities, for which more attention was required. While physical therapists have also used walking-related therapeutic techniques with stroke patients [ 35 , 36 ]. Nevertheless, the findings of this study will not only help identify the difference in effects caused by supervised group-based walking and non-supervised individual-based walking interventions, but they will also create awareness in Saudi Arabia among government and the general public about the ageing problem and ways to improve intervention outcomes.…”
Section: Methodsmentioning
confidence: 99%